The Development Of Steering Indicators In Public Entreprises In Cameroon: An Implementation Based On Contengency Factors - Francois-Xavier, Professor Mayegle; Noe, Dr Ndjeck; Souaibou, Saidou (The journal of contemporary issues in business and government, 2021)
Based on the results from an empirical research, this article aims to determine on the one hand the nature of the indicators developed in dashboards of public enterprises and to verify on the other hand the link between certain contingency factors and the steering indicators developed in the dashboards of 32 Cameroonian public enterprises. The results of this research show firstly that the dashboards of public enterprises are moderately "balanced" and the commonly used indicators are financial in nature. Secondly, it is noted that only contingency factors such as size, business sector and public participation have a positive and significant link with the balance of the scoreboards of Cameroonian public enterprises.